2012
DOI: 10.3390/nu4111610
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Interactions with Soy Isoflavones on Bone after Menopause: A Review

Abstract: Vitamin D is known to increase Ca absorption in adults. However, the threshold vitamin D status to benefit Ca absorption is lower than the target vitamin D status for higher bone mineral density and lower fracture risk, pointing to another pathway for vitamin D to benefit bone. One possibility is by affecting osteoblast and osteoclasts directly. Vitamin D-related bone metabolism may also be affected by soy isoflavones, which selectively bind to the estrogen receptor β and may reduce bone loss in postmenopausal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 64 publications
0
17
0
3
Order By: Relevance
“…Chacun de ces micronutriments joue un rôle important dans le métabolisme de l'organisme. Le calcium a un effet sur la santé des os en termes de protection (Park et Weaver, 2012) ; le magnésium peut faire baisser la tension artérielle, le taux du cholestérol et est impliqué dans les systèmes de défenses naturelles contre les agressions de toute sorte ; il est très important pour la femme enceinte (Sidor et al, 2016). Le fer a un rôle essentiel dans le métabolisme des globules rouges (hémoglobine), dans la fonction musculaire.…”
Section: Composition En Oligoélémentsunclassified
“…Chacun de ces micronutriments joue un rôle important dans le métabolisme de l'organisme. Le calcium a un effet sur la santé des os en termes de protection (Park et Weaver, 2012) ; le magnésium peut faire baisser la tension artérielle, le taux du cholestérol et est impliqué dans les systèmes de défenses naturelles contre les agressions de toute sorte ; il est très important pour la femme enceinte (Sidor et al, 2016). Le fer a un rôle essentiel dans le métabolisme des globules rouges (hémoglobine), dans la fonction musculaire.…”
Section: Composition En Oligoélémentsunclassified
“…Soy also increases ERb expression that lead to an increase in the expression of vitamin D (VD) receptor and VD metabolites in osteoblastic cells, so soy and VD can synergistically stimulate bone formation [66]. Regarding bone resorption, soy enriched diet decreased serum cathepsin k level and downregulated the expression of bone cathepsin k mRNA in diabetic rats due to inhibition of the tyrosine-specific protein kinase activity of the epidermal growth factor (EGF) receptor on osteoclasts cells that results in decreased osteoclastic protein synthesis [67].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that isoflavones increase vitamin D receptor expression on the cell surface and, thus, could potentiate the action of vitamin D [24]. Furthermore, it has been found that isoflavones can inhibit the CYP24 enzyme, which is involved in the degradation of 1,25-dihydroxycholecalciferol and its precursor 25-hydroxycholecalciferol, which would increase plasma levels [10].…”
Section: Discussionmentioning
confidence: 99%